Ab inito and FTIR Studies of HfSiCNO Processed from the Polymer Route. Issue 3 (6th January 2014) - Terauds, Kalvis; Raj, Rishi; Kroll, Peter; Soraru, G.
<x xml:space="preserve">Abstract</x> The reactions between polysilazane and hafnium‐butoxide precursors are followed from the liquid, to the cross‐linked, and finally to the ceramic state by infrared spectroscopy. We find evidence of formation of Hf–N bonds in the liquid state, and Hf–O–Si bonds in the cross‐linked polymer state. Results from ab inito calculations for the ceramic state are presented. They show that Hf behaves like Si, forming bonds with C, N, and O in proportion of the Hf/Si ratio in the compounds. The average values of such bonds formed by Hf, relative to silicon, are 11.2, 17.8, and 24.4%, which is in reasonable agreement with the overall Hf/Si ratio in the samples (8%, 15% and 22%). It is concluded that it is appropriate to express the composition of these compounds in terms of the Hf/Si ratio. The X‐ray data that show the emergence of weak diffraction peaks for monoclinic HfO2 when the Hf/Si ratio is 0.22, but not at lower concentrations of Hf [K. Terauds and R. Raj, J. Am. Ceram. Soc., 96, 2117–2123 (2013)].